SIMULASI ANALISIS KELAYAKAN USAHA BUDIDAYA IKAN BANDENG (Chanos chanos) KUARTAL PERTAMA TAHUN 2022 - Muh. Sulaiman Dadiono; Rudy Wijaya; Rima Oktavia Kusuma; Aminin Aminin (Jurnal Perikanan Pantura (JPP), 2023)
In the first quarter of 2022 (1 January – 31 March) in Indonesia, there are problems related to the increase in the prices of basic necessities which can increase the amount of initial capital needed in a milkfish (Chanos-chanos) cultivation business. So it is necessary to conduct an initial simulation study of the feasibility analysis of milkfish cultivation to determine the capital and business feasibility for milkfish cultivation in the first quarter of 2022. The method used in this study is a library research method, where the data collection method is entirely with data. Secondary or literature study. Secondary data is collected by reviewing from references in the form of journals, books, and online articles that are still related. The calculation of business feasibility analysis is carried out by calculating investment costs, fixed costs, variable costs, calculating production costs, revenues, profits, BEP Rupiah, BEP Units, R/C Ratio, and PBP. Furthermore, an analysis of the supporting and inhibiting factors of the business as well as an analysis of the marketing strategy in the milkfish cultivation business was carried out. The results of the calculation of business feasibility simulations show that the production cost is Rp. 78.276.800, revenue is Rp. 1.344.000.000, profit is Rp. 950.861.600, Rupiah BEP is Rp. 192.549.566, which means the turning point will be achieved if sales reach Rp. 192.549,566. , BEP Unit is 9627 fish, which means the turning point will be reached if milkfish production reaches 9,627 fish. The R/C Ratio obtained is 1.7 and the PBP is 0.3 years, where the investment capital of this milkfish cultivation business will return within a period of 0.3 years or 3.6 months. Therefore, the milkfish cultivation business for the first quarter of 2022 can be said to be profitable and feasible to run.